Research on the Prepositive Distance of Crosswalk Warning Markings for Unsignalized Road Section - Guohua Liang; Fangfang Wang; Quan Shi; Rui Li; Zhijing Ji; Chenchen Dong (Journal of Advanced Transportation)
This paper proposed an optimal prepositive distance of crosswalk warning markings for unsignalized road section under three different design speeds based on the mathematical modelling and driving simulation. To set up the most efficient mathematical modelling for calculating the layout interval of prepositive distance, the vehicles slowing down behaviour characteristics in front of crosswalk were explored. According to the layout interval, the simulation experiment was carried out in the UC-win/Road version 13.0 driving simulator. The rate of speed reduction and the times of maximum deceleration obtained from simulation experiments were selected as evaluation indicators to compare and analyse the deceleration effect related with the prepositive distances of the crosswalk warning markings under three design speeds. The results show that when the design speeds are 30 km/h, 40 km/h, and 50 km/h, the optimal prepositive distances of the crosswalk warning markings are 30 m, 40 m, and 60 m, respectively.